2021
DOI: 10.1109/access.2021.3104999
|View full text |Cite
|
Sign up to set email alerts
|

Current Harmonic Mitigation Using a Multi-Vector Solution for MPC in Six-Phase Electric Drives

Abstract: Multiphase machines offer some interesting features to develop more-competitive electric drives. However, the control complexity increases due to the higher number of freedom degrees. Specifically, the regulation of secondary currents becomes critical to avoid an unacceptable harmonic distortion of phase currents. In this regard, standard finite-control-set model predictive control (FCS-MPC) is characterized by a limited capability to provide a suitable current quality, since a single switching state is applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, MPC based on the application of a single switching state per control period presents an unacceptable current quality. Fortunately, this undesirable harmonic content has been mitigated with the development of multi-vector solutions [22][23][24][25][26][27][28][29][30][31][32][33]. In fact, ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, MPC based on the application of a single switching state per control period presents an unacceptable current quality. Fortunately, this undesirable harmonic content has been mitigated with the development of multi-vector solutions [22][23][24][25][26][27][28][29][30][31][32][33]. In fact, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the selected family of controllers, it can be concluded that the last decade has witnessed success, where a high number of more competitive control techniques have been developed in diverse application fields such as renewable energy application [34] or electrical propulsion [35,36]. The most popular procedure in the field of electric drives to illustrate the goodness of an original proposal of the state of the art is an experimental comparison using a benchmark method as a basis for the verification [23][24][25][26][27][28][29][30][31][32][33]37,38]. Focusing on the necessary validation process, it is also common to carry out the mentioned comparison on a single test bench where the electric machine is characterized by specific values of its electrical parameters [18,20,[22][23][24][25][26][27]31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A constant current/voltage control strategy with the interleaving modulation technique has been proposed in Subotic et al 1 to meet the grid standards. A simplified direct torque control (DTC) strategy has been introduced in Pandit et al 2 Furthermore, a predictive control strategy, 3 modulated model predictive control (M 2 PC) method, 4 an intelligent voltage vectors‐based model predictive control (MPC) routine, 5 current harmonic mitigation method using a multi‐vector solution, 6 and a predictive DTC strategy with fault‐tolerant function 7 have been reported for six‐phase induction machines.…”
Section: Introductionmentioning
confidence: 99%
“…One of the silent characteristics of SPIM is the poor quality of phase current waveform due to circulating 𝑥𝑥𝑥𝑥 current components, which is even more problematic under direct controllers, such as model predictive control (MPC) [14,17]. The available literature has proposed two approaches to tackle this problem: enhanced machine design-based and enhanced control-based approaches.…”
Section: Introductionmentioning
confidence: 99%